Spinal ultrasound imaging implied the vascular dynamics in chronic and acute pain - Yingzhuo Ding; Chunxia Yu; Qingqing Chi; Mengjiao Deng; Dongxia Duan; Jinbao Wei; Yufei Xi; Qin Li; Le Ma (MethodsX)
Neurovascular coupling links local neural activity to cerebral blood flow changes, crucial for pain transduction. In this undertaking, we present an advanced spinal functional ultrasound imaging that exhibits precise observation capabilities of the influence of analgesic medications on spinal cord blood flow, encompassing both acute and chronic pain scenarios. Utilizing gabapentin as the primary analgesic agent, we have observed that intrathecal administration of gabapentin notably augments the blood flow intensity in neuropathic rats while exerting minimal influence on the blood flow of the sham rats. Furthermore, subcutaneous formalin injection increases spinal cord blood flow, but gabapentin pretreatment prevents those effects. These findings demonstrated the analgesic effect of gabapentin exhibits a synergistic interaction with the intensity of blood flow around neurons, which is crucial for understanding the mechanisms underlying the occurrence of pain. In this article, we show:• A simple method to build the spinal cord ligation-induced chronic pain model.• A generic way to build the formalin-induced acute pain model.• An optimized functional ultrasound imaging technique in chronic and acute pain.